COMPERATIVE OF PRIM’S, KRUSKAL’S AND BORUVKA’S ALGORITMA TO SOLVE MINIMUM SPANNING TREE PROBLEMS - Faridawaty Marpaung; Arnita Arnita; Wirdatull Jannah Idris (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract. Optimization is important in an algorithm. It can save the operational costs of an activity. In the Minimum Spanning Tree, the goal is to achieve how all vertices are connected with the smallest weights. Several algorithms can calculate the use of weights in this. The purpose of this study is to find out the Primary electricity distribution network graph model and  correct algorithm to determine the minimum spanning tree. By comparing three algorithms, Prim’s, Boruvka’s and Kruskal’s algorithm, it will get an efficient algorithm to solve the minimum spanning tree problem. To get the output it takes several steps: Data collection: Designing Model: calculating the minimum spanning tree of Prim’s, the Boruvka’s and Kruskal’s algorithm: Comparing the efficiency of each algorithms. The analysis shows that the Prim’s and Bruvka’s and Kruskal’s algorithm have different steps even though the final result in the form of weights obtained in achieving the minimum spanning tree is the same. But in the case of electric network optimization, the Prim’s algorithm is more efficient in installing of primary electricity distribution in Gand Asia City at Labuhan Ruku by PT.PLN branch Tanjung Tiram, Batubara district. Keywords: Minimum spanning tree, Prim’s Algorithm, Boruvka’s Algorithm,Kruskal’s Algorithm Abstrak. Optimasi adalah hal penting dalam suatu algoritma. Ini dapat menghemat biaya operasional suatu kegiatan. di Minimum Spanning Tree, yang ingin dicapai adalah bagaimana semua vertex terhubung dengan bobot terkecil. Beberapa algoritma dapat menghitung penggunaan bobot dalam graf ini. Tujuan penelitian ini mengetahui Model graf jaringan distribusi listrik primer serta algoritma yang tepat untuk menentukan minimum spanning tree. Dengan membandingkan tiga buah algoritma yaitu algoritma Prim, algoritma Boruvaka dan algoritma Kruskal  akan diperoleh algoritma yang efisien menyelesaikan masalah nimimum spanning tree. Untuk mendapatkan outputnya diperlukan beberapa tahap:  Pengumpulan data : Merancang Model : Mencari minimum spanning tree dari algoritma Prim, algoritma Boruvka dan algoritma Kruskal : Membandingkan keefisienan masing masing algoritma. Dari hasil analisis menunjukkan bahwa algoritma Prim dan  algoritma Boruvka dan algoritma Kruskal memiliki langkah yang berbeda – beda meskipun hasil akhir berupa bobot yang diperoleh dalam mencapai penyelesaian minimum spanning tree  adalah sama . Namun dalam kasus optimasi jaringan listrik algoritma Prim yang lebih efisien. untuk pemasangan distribusi listrik primer di Perumahan Grand Asia City di Labuhan Ruku oleh  PT.PLN cabang Tanjung Tiram Kabupaten Batubara. Kata Kunci : Minimum spanning tree, Algoritm Prim, Algoritma Boruvka , Algoritma Kruskal